KEMAMPUAN RETENSI DAN TRANSFER BELAJAR MAHASISWA DARI SKEMA DIFERENSIAL KEDALAM KONTEKS PEMECAHAN MASALAH FISIKA - Ngadimin Ngadimin (JURNAL FISIKA EDUKASI, 2014)
The research intends to develop asessment about retention and learning transfer, spesifically,  aims to identify retention and learning transfer of students from differential scheme into physics problems solution; identify students’ difficulties in doing learning transfer from differential scheme into the context of Physics problems. This research used instrument in forms of written test and questionaire. The test is macth questions.  Every match question is consisted of a pure differential question and a physics problem that applies relevant differential concept. It is used Pearson Corelation test to identify learning transfer. Corellation test toward the test, shows that high correlation toward simple and similar match questions. In constrats, it shows low correlation toward difficult match question and needs concept analyisis to construct physics problem into diffetial equation. The correlation indicates learning transfer from differetial equation context into physics problem solutions that utilize differential equation context. There are several factors cause students’ difficulties  in doing learning transfer namely: notation changes, disturbance of wrong assumptions from previous learnt concept, difficulty in constructing physics problem which is stated in narratif form to be solved diffential equation.